COMPENSATION FOR BUSINESS TENANTS: MISCHIEF AND MALADY. (November 2020) - Haley, Michael
Abstract: This article focuses upon the provisions and underlying policy of the Landlord and Tenant Acts of 1927 and 1954. It surveys the mischief that each Act was designed to address and, from the perspective of compensation for business tenants, examines critically the legislative response. It demonstrates that the safeguards afforded by the 1927 Act were poorly conceived, ill-constructed and ineffectual. Although the 1954 Act was intended to instil simplicity, certainty and fairness, it fails on all counts. The law remains highly technical, unduly complex, arbitrary in operation and in need of major overhaul.